Directed transport induced by α-stable Lévy noises in weakly asymmetric periodic potentials - Risau Gusman, Sebastian Luis (2013)
Fil: Risau Gusman, Sebastian Luis. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina